2014
DOI: 10.1016/j.gaitpost.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic instability during post-stroke hemiparetic walking

Abstract: Falls and fall-related injuries cause extremely costly and potentially fatal health problems in people post-stroke. However, there is no global indicator of walking instability for detecting which individuals will have increased risk of falls. The purposes of this study were to directly quantify walking stability in stroke survivors and neurologically intact controls and to determine which stability measures would reveal the changes in walking stability following stroke. This study thus provided an initial ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
134
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(146 citation statements)
references
References 34 publications
9
134
3
Order By: Relevance
“…This measure is based on foot placement while accounting for body CoM position and velocity and has been used to assess dynamic balance in young healthy individuals in destabilizing environments (e.g., McAndrew Young et al, 2012), older adults while stepping to targets (Hurt and Grabiner, 2015), amputees (e.g., Bolger et al, 2014; Gates et al, 2013; Hof et al, 2007) and post-stroke individuals (e.g., Hak et al, 2013; Kao et al, 2014). Similarly, whole-body angular-momentum has been used to assess dynamic balance in a number of patient populations including post-stroke hemiparetic individuals (Nott et al, 2014), amputees (e.g., Pickle et al, 2014; Sheehan et al, 2015; Silverman and Neptune, 2011) and older adults (e.g., Pijnappels et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…This measure is based on foot placement while accounting for body CoM position and velocity and has been used to assess dynamic balance in young healthy individuals in destabilizing environments (e.g., McAndrew Young et al, 2012), older adults while stepping to targets (Hurt and Grabiner, 2015), amputees (e.g., Bolger et al, 2014; Gates et al, 2013; Hof et al, 2007) and post-stroke individuals (e.g., Hak et al, 2013; Kao et al, 2014). Similarly, whole-body angular-momentum has been used to assess dynamic balance in a number of patient populations including post-stroke hemiparetic individuals (Nott et al, 2014), amputees (e.g., Pickle et al, 2014; Sheehan et al, 2015; Silverman and Neptune, 2011) and older adults (e.g., Pijnappels et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, gait characteristics of stroke survivors have also been shown to predict falls (16). Moreover, with regard to gait stability, it has been shown that the local divergence exponent (LDE) was larger in stroke survivors than in age-matched healthy peers (17), indicating less stable gait. Still, stroke survivors had equal margins of stability (MoS) (17) probably accomplished by a larger step width (18).…”
mentioning
confidence: 99%
“…During the usual straight line walking, spatiotemporal variabilities have been known to be an early indicator of mobility impairment and associated with risk of falls. Stroke survivors show decreased gait velocity, asymmetric walking pattern, and increased step width, and thereby show a different walking pattern compared to before the stroke event [14]. Spastic or synergistic gait patterns are atypical movement patterns in hemiparetic stroke patients and include contact with ground via toe strike or foot flat, loss of hip extension, and usage of excessive forward trunk flexion to initiate [1].…”
Section: Discussionmentioning
confidence: 99%